2020
DOI: 10.1007/jhep01(2020)055
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form expression for cross-channel conformal blocks near the lightcone

Abstract: In the study of conformal field theories, conformal blocks in the lightcone limit are fundamental to the analytic conformal bootstrap method. Here we consider the lightcone limit of 4-point functions of generic scalars. Based on the nonperturbative pole structure in spin of Lorentzian inversion, we propose the natural basis functions for cross-channel conformal blocks. In this new basis, we find a closed-form expression for crossed conformal blocks in terms of the Kampé de Fériet function, which applies to int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…In [17,25,[27][28][29] it was revealed that performing the full inversion formula gives rise to new non-perturbative corrections in the large-spin expansion. One question is if these corrections play any important role in the large spin sums considered here.…”
Section: Double-twist Improvement (Dti)mentioning
confidence: 99%
“…In [17,25,[27][28][29] it was revealed that performing the full inversion formula gives rise to new non-perturbative corrections in the large-spin expansion. One question is if these corrections play any important role in the large spin sums considered here.…”
Section: Double-twist Improvement (Dti)mentioning
confidence: 99%
“…Refs. [78,79,80,27,17,76,81,82] -especially because the p-adic analog of these methods yields, promisingly, a closed-form expression for the crossed channel decomposition of the four-point exchange diagram on the Bruhat-Tits tree [72].…”
Section: Spectral Decomposition Of Ads Diagramsmentioning
confidence: 99%
“…Recently, progress has also been made in obtaining relations obeyed by the decomposition coefficients of four-point exchange diagrams in the crossed channel[77,78,79,80,27,17,76,81,82] but in this paper we will restrict our discussion to only direct channel decomposition 6. In AdS 3 /CFT 2 , various limits of Virasoro blocks, obtained by taking particular heavy/light limits of dimensions of external operators, are also interpreted in terms of lengths of bulk geodesics and as geodesic diagrams in defect geometries[62,93,94,95,96]).…”
mentioning
confidence: 99%
“…Unlike the parity-even case, parity-odd families have non-zero off-diagonal components: . To calculate the scalar coefficients dp J,0 i we will use the Lorentzian inversion formula [9,12,16], combined with either dimensional reduction of the 3d block [16,32] or resummations of the lightcone expansion [20]. Using dimensional reduction we find for the n = 0 doubletwist operators:…”
Section: Jhep09(2020)148mentioning
confidence: 99%
“…ψψO 6 come at subleading order. 20 By dividing by the MFT coefficients given in (4.18), we obtain the anomalous dimension at large spin:…”
Section: Jhep09(2020)148mentioning
confidence: 99%